Perception of Local Communities and Management Strategy of Community-based Marine Protected Area (MPA) in the Spermonde Archipelago (Case Study: Mattiro Baji Village, Pangkep Regency) - Tamti, Hartati; Indar, Yusran Nur (Journal of Indonesian Coral Reefs, 2012)
This is research aimed to (1) analyze communityÃ¢â¬â¢s perception regarding the existence of coral reef resources in Mattiro Baji Village, (2) analyze various issues in relation to establishment and management strategy of community-based Marine Protected Area (MPA). This research uses in-depth interview and Participatory Rural Appraisal (PRA) methods. From the analyses it is concluded that (1) the perception of local community regarding the importance of coral reef ecosystem value is excellent, even though it is not fully implemented yet in their daily life, (2) Several key factors supporting the existence of CBMPA in Mattiro Baji include (a) community understanding about the need to MPA is relatively good, (b) there is a valuable lesson learned regarding the destruction of coral reef ecosystem, and (c) the unity spirit among community to protect and manage the resources from outsiders. Various strategies need to be conducted for the MPA development such as the establishment of waters boundary and the use of village area, zonation management, monitoring and surveillance of areas utilization and MPA, the increase of community understanding to environment, community efforts and incomes through alternative income generation activities.